Pengaruh Pelatihan Team Building TerhadXKohesivitas Tim Marketing pada PTX - Rahma Hidayati; Kamsih Astuti; Reni Yuniasanti (Jurnal Psikologi, 2020)
This study aims of this research is to find out the effect of team building training toward team’s cohesiveness in the marketing divisionof PTX. There are 24 Subjects of this research divided into two group consist of 12 people in theexperiment groups and 12 people in the control group using random assignment as sample collection technique with valid and reliable cohesiveness scale as data collection technique. The data analysis technique of this research was using Paired Sample T Test.The subjects of this study is marketing division’s employees of PT. X, aged between18-35 years with low and medium cohesiveness. The design of this research was using pretest posttest control group design. The comparative test was using Paired Sampel T Test to compare the difference toward experiment group before and after training obtained (t=8,210 and p = 0,000; p < 0,001). It means that there is distinctive cohesiveness score of the team before and after the team building training. Furthermore, the result of using Independent Sampel T Test to compare these experiment and control group is t = 4.386 and p = 0.000 (p<0.01), MD 48.50, 37.83). It means that the cohesiveness of experiment group is higher compared to control group after team building training.